Communities as Critical Partners in Teacher Education: The Impact of Community Immersion on Teacher Candidatesâ Understanding of Self and Teaching in Urban Schools - Jennifer H. Waddell (Arizona State University, 2013)
Communities play a critical role in helping teacher candidates understand the social and historical aspects of community and their impact on schools, students and families, particularly in urban communities. Communities should be integral and equal partners in preparing teachers for today's diverse schools. This paper focuses on utilizing the community as a space for preparing urban teachers. It describes a study of an urban community immersion experience in teacher education at a predominantly white institution. This qualitative study was guided by two research questions, "How have these community immersion experiences influenced candidates' understanding of self?" and "How have these experiences influenced candidates' identity as a teacher in urban schools?" Findings suggest that carefully designed community experiences can have significant impact on teacher candidates' understanding of self and their identity as teachers in urban schools.